2021
DOI: 10.1055/a-1345-9821
|View full text |Cite
|
Sign up to set email alerts
|

Telomere Length in Idiopathic Recurrent Pregnancy Loss

Abstract: Objective Telomere length is used as an indicator of biological aging. It is well known that one of the most remarkable risk factors of recurrent pregnancy losses is advanced maternal age. The objective of this study was to investigate the correlation between idiopathic recurrent pregnancy loss and telomere length. Method The study group included 40 women, while the control group consisted of 41 healthy women whose age and body mass index were matched. A venous blood sample was taken from all participants into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Our findings that a shortened TL was correlated with an increased risk of SA were consistent with those of prior research. For instance, a recent case-control study found that women with iRPL (n=40) had significantly shorter peripheral blood leukocyte TL in early follicular stages than healthy women (n=41) with a comparable age and body mass index (P=0.006) (43). In studies of infertile women undergoing in vitro fertilization (IVF), shorter peripheral blood leukocyte TL was linked with a higher incidence of embryonic aneuploidy, a major contributor to pregnancy loss (P=0.01) (44).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings that a shortened TL was correlated with an increased risk of SA were consistent with those of prior research. For instance, a recent case-control study found that women with iRPL (n=40) had significantly shorter peripheral blood leukocyte TL in early follicular stages than healthy women (n=41) with a comparable age and body mass index (P=0.006) (43). In studies of infertile women undergoing in vitro fertilization (IVF), shorter peripheral blood leukocyte TL was linked with a higher incidence of embryonic aneuploidy, a major contributor to pregnancy loss (P=0.01) (44).…”
Section: Discussionmentioning
confidence: 99%
“…Strikingly, in tubal pregnancies, which are a type of ectopic implantation caused by zygotes fixed outside the uterine cavity [79], the telomere length of placenta samples was similar to controls [80 ▪ ]. Finally, LTL was found to be shorter in women with idiopathic recurrent pregnancy loss [81].…”
Section: Uterine Aging and Implantationmentioning
confidence: 99%